Corporate governance and audit report timeliness: evidence from Malaysia - Puat Nelson, Sherliza; Shukeri, Siti Norwahida (Emerald Group Publishing Limited, 2011)

(untitled)
Purpose : The purpose of this study is to examine the impact of corporate governance characteristics on audit report timeliness in Malaysia. The corporate governance characteristics examined are board independence, audit committee size, audit committee meetings and audit committee members’ qualifications. Design/methodology/approach : The sample comprises of 703 Malaysian listed companies from Bursa Malaysia for the year 2009. It excludes companies from finance related sector as they operate under a highly regulated market under the supervision by the Central Bank of Malaysia. Further, regression analysis was performed to examine the audit report timeliness determinants. Findings : Results show that audit report timeliness is influenced by audit committee size, auditor type, audit opinion and firm profitability. However, no association was found between board independence, audit committee meetings and audit committee members’ qualifications and audit report timeliness. Research limitations/implications : Practical implication may be suggested on a minimum submission period of audit report, and regulators’ support for organisation to have larger audit committee size. Originality/value : The study investigates the impact of corporate governance on audit timeliness, in light of the recent amendments on the Malaysian Code of Corporate Governance made in 2007.